Nationalism by design the politics of dress in British Burma - Edwards, Penny (SPAFA Journal : a publication of the SEAMEO Regional Centre for Archaelogy and Fine Arts)
Colonial attempts to hem in racial and gender difference through practice, law and lore made dress a potent field of resistance in British Burma, giving rise to new strands of nationalism by design.